Seasonal Variations in Fat and Fatty Acid Profiles of Barbus tauricus (Kessler, 1877) From Duzce-Melen Basin (Turkey) - Şerife Gülsün Kırankaya; Deniz Ayas; Deniz Yağlıoğlu (Düzce Üniversitesi Bilim ve Teknoloji Dergisi)
In this study, total lipid and fatty acid profiles of Barbus tauricus samples which were obtained from Melen River Basin during winter, spring, and summer seasons, were evaluated. Total lipid levels were determined 2.27%, 2.37%, and 4.34% in winter, spring, and summer, respectively. The study also determined that the carbon count of 30 fatty acids, composing total fat compositions of B. tauricus caught in Melen Basin, ranges among 12-24. The major fatty acids of B. tauricus are palmitic acid and stearic acid from SFA; palmitoleic acid, trans oleic acid, oleic acid and erucic acid from MUFA and linoleic acid, alfa linolenic acid, eicosapentaenoic acid and docosahexaenoic acid from PUFA. The study is the first one on lipid and fat profiles of B. tauricus, one of the species living in Duzce Melen Basin and having high economic importance, and aimed to investigate total lipid and fatty acid profiles according to the season.